Analysis of the Effect of Ethical and Benevolent Leadership on Job Satisfaction Mediated by Loyalty to Supervisors - Melia Dianingrum; Bilqis Hifdhillah (Majalah Ilmiah Bijak, 2021)
The development of a company depends on the leadership's ability to carry out their duties. The company's success can be achieved if good cooperation between the leaders and subordinates is carried out. Good collaboration between leaders and subordinates does not guarantee job satisfaction. This research aims to analyze the relationship between ethical leadership, benevolent leadership, and job satisfaction mediated by loyalty to supervisors. The research method used the purposive sampling method. Methods of data analysis using SMARTPLS with 75 respondents from 3 private companies operating in Purwokerto, Central Java. Data collection methods: observation, interviews, online questionnaires. The results showed that there was a significant influence between ethical leadership, benevolent leadership on loyalty to supervisor, there was a significant relationship between ethical leadership on job satisfaction, job satisfaction was not influenced by benevolent leadership, there was a significant influence between beenvolent leadership on job satisfaction mediated by loyalty to supervisor.